Statistics on Public Expenditures for Economic Development (SPEED): Evaluation of outcomes based on the use of the SPEED database, 2008–2018 - Lowder, Sarah K. (International Food Policy Research Institute, 2019)
This report evaluates the use of one of IFPRI’s flagship products, the Statistics on Public Expenditures for Economic Development1 (SPEED), which has been supported by the CGIAR Research Program on Policies, Institutions, and Markets (PIM) since 2012. SPEED comprises a database on public expenditures, tools to visualize and manipulate the data, and reports that draw upon the data. The 2015 (latest) version of SPEED contains information from 10 public expenditure sectors in 147 countries from 1980 to 2012 (IFPRI 2015). The sectors are agriculture, communication, education, defense, health, mining, social protection, fuel and energy, transport, and transport and communication (as a group). IFPRI researchers have compiled data from multiple sources, including the International Monetary Fund (IMF), the World Bank, and national governments, and conducted extensive data checks and adjustments to ensure spending measurements that are consistent over time and free of exchange-rate fluctuations and currency denomination changes. This report also considers the use of the 2010 and 2013 versions of the SPEED database, which contain fewer sectors, feature country coverage that is less broad, and span fewer years than the 2015 edition (see IFPRI 2010 and IFPRI 2013).